2002
DOI: 10.1092/chwk-gmq0-mlke-k03v
|View full text |Cite
|
Sign up to set email alerts
|

Board Characteristics and Audit Fees

Abstract: This paper examines the relations between three board characteristics (independence, diligence, and expertise) and Big 6 audit fees for Fortune 1000 companies. To protect its reputation capital, avoid legal liability, and promote shareholder interests, a more independent, diligent, and expert board may demand differentially higher audit quality (greater assurance, which requires more audit work) than the Big 6 audit firms normally provide. The audit fee increases as the auditor's additional costs are passed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
221
4
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(271 citation statements)
references
References 12 publications
34
221
4
6
Order By: Relevance
“…[15] and [12] found that audit committee independence has a significant and positive relationship with audit fees. However, this finding contrasted that of [11,14,17]. The results found in [12] on the relationship between audit committee expertise and audit fees also contrasted with the findings of [13,16,15,17].…”
Section: Introductioncontrasting
confidence: 61%
See 4 more Smart Citations
“…[15] and [12] found that audit committee independence has a significant and positive relationship with audit fees. However, this finding contrasted that of [11,14,17]. The results found in [12] on the relationship between audit committee expertise and audit fees also contrasted with the findings of [13,16,15,17].…”
Section: Introductioncontrasting
confidence: 61%
“…The results found in [12] on the relationship between audit committee expertise and audit fees also contrasted with the findings of [13,16,15,17]. Similarly, [15] and [17] found that the frequency of audit committee meetings has a significant and positive relationship with audit fees did not support the findings of [11] and [12]. In the study of [12], there was no evidence to show that board independence has a significant relationship with audit fees; this result was not supported by [13,15,17].…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations